Proteomic profile of the venom of three dark-colored Tityus (Scorpiones: Buthidae) from the tropical rainforests of Costa Rica - Díaz Oreiro, Cecilia (2023)
Objective: We aimed to elucidate the potential differences in the venom peptide sequences of three Tityus species from Costa Rican rainforests: T. jaimei, T. championi and T. dedoslargos, compared to T. cf. asthenes from Colombia, which could explain the low level of scorpionism in Costa Rica, evidenced by the lack of epidemiological data. Methodology: We applied venom proteomics of peptides purified by RP-HPLC and compared the obtained sequences from venoms of these Tityus species to the sequences previously identified from Tityus inhabiting other Central and South American regions. Results: Venom proteome analysis evidences that most of the putative peptide toxins identified in Costa Rican dark-colored Tityus are very similar to those present in other T. (Atreus) from the region. Conclusions: Our study suggests that, in the case of potential envenomation by Tityus in Costa Rica, the same level of toxicity should be observed, compared to other cases caused by members of the subgenus from other geographical localities. On the other hand, compared to countries with more accelerated urban expansion, Costa Rican Tityus still inhabit secondary rainforests and do not commonly share the same spaces with humans, so the lack of epidemiological evidence of medical emergencies caused by envenoming by this scorpion group could be more related to ecological and demographic factors and less attributed to the characteristics of the venom.